2013
DOI: 10.1001/jamapediatrics.2013.417
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Food and Full-Service Restaurant Consumption Among Children and Adolescents

Abstract: Objective To examine the impact of fast-food and full-service restaurant consumption on total energy intake, dietary indicators and beverage consumption. Design Individual-level fixed effects estimation based on two non-consecutive 24-hour dietary recalls. Setting Nationally representative data from the 2003–2004, 2005–2006, and 2007–2008 National Health and Nutrition Examination Survey. Participants Children aged 2 to 11 (N=4717) and adolescents aged 12 to 19 (N=4699) Main Outcome Measures Daily total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
230
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(258 citation statements)
references
References 29 publications
(46 reference statements)
14
230
0
4
Order By: Relevance
“…Despite the importance of cooking in modern life, little is known about behaviours and perceptions of cooking in the USA; much less is known about this critical intermediate step than is known about either food access or consumption (1)(2)(3)(4)(5)(6)(7) . Available evidence suggests that adults in the USA spend less time cooking now than in the past (8,9) .…”
mentioning
confidence: 99%
“…Despite the importance of cooking in modern life, little is known about behaviours and perceptions of cooking in the USA; much less is known about this critical intermediate step than is known about either food access or consumption (1)(2)(3)(4)(5)(6)(7) . Available evidence suggests that adults in the USA spend less time cooking now than in the past (8,9) .…”
mentioning
confidence: 99%
“…Previous research has confirmed that both fast food and full-service restaurant dining are associated with higher energy intake and poorer diet quality [3,7,21]. However, prior studies have produced conflicting findings regarding children's dining choices and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to the excess total caloric intake associated with fastfood consumption for children and adolescents (126 and 310 kcal, respectively). 10 In both cases, other sources of caloric intake are not sufficiently reduced to balance overall calories. The effect of pizza on total excess caloric intake was found to be consistent across gender, race, and income, with the exception that it was significantly higher for black compared with Hispanic children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that on the days that sugar-sweetened beverages or fast food are consumed by children, overall caloric intake is increased. 10,11 To explore whether a similar effect exists for pizza, we estimated individual-level fixed effects regression models by using dietary recall data to examine the relationship between any pizza consumption (including by meal occasion and source) and total energy intake (TEI) and indicators of diet quality. We also examined whether the impact of pizza consumption on overall energy intake differed by gender, race/ethnicity, and socioeconomic status (SES).…”
Section: What This Study Addsmentioning
confidence: 99%